Extracellular Matrix-Based Biomaterials for Cardiovascular Tissue Engineering - Khanna, Astha; Zamani, Maedeh; Huang, Ngan F. (Journal of cardiovascular development and disease, 2021)
Regenerative medicine and tissue engineering strategies have made remarkable progress in remodeling, replacing, and regenerating damaged cardiovascular tissues. The design of three-dimensional (3D) scaffolds with appropriate biochemical and mechanical characteristics is critical for engineering tissue-engineered replacements. The extracellular matrix (ECM) is a dynamic scaffolding structure characterized by tissue-specific biochemical, biophysical, and mechanical properties that modulates cellular behavior and activates highly regulated signaling pathways. In light of technological advancements, biomaterial-based scaffolds have been developed that better mimic physiological ECM properties, provide signaling cues that modulate cellular behavior, and form functional tissues and organs. In this review, we summarize the in vitro, pre-clinical, and clinical research models that have been employed in the design of ECM-based biomaterials for cardiovascular regenerative medicine. We highlight the research advancements in the incorporation of ECM components into biomaterial-based scaffolds, the engineering of increasingly complex structures using biofabrication and spatial patterning techniques, the regulation of ECMs on vascular differentiation and function, and the translation of ECM-based scaffolds for vascular graft applications. Finally, we discuss the challenges, future perspectives, and directions in the design of next-generation ECM-based biomaterials for cardiovascular tissue engineering and clinical translation.